Dark side of social media and academic performance of public sector schools students: Role of parental school support. Issue 3 (5th December 2019) - Raza, Muhammad Yousaf; Khan, Ali Nawaz; Khan, Naseer Abbas; Ali, Ahsan; Bano, Shehar
Abstract : Students are regularly engaged in several things at the same time during class and school time. They are using smartphones, tablets, laptops, and using social media on these devices while learning and attending class. However, there are some situations likely influenced by this, current study tests the influence of technostress, cyberbullying, and media multitasking in the context of students in technology‐saturated classrooms and how this is affecting their academic performance. This study further explored the buffering effects of parental school support on the relationship between technostress, cyberbullying, and student's performance. By using the person‐environment fit model, this study surveyed 248 public sector school students in two waves and examined the impact of these variables on student's academic performance. Results show that technostress, cyberbullying, and media multitasking have a negative impact on student performance, and school parental support moderates the negative relationship between technostress and student performance. Implications and contributions have also been discussed.